Impact of Gut Microbiome on Hypertensive Patients With Low-Salt Intake: Shika Study Results - Nagase, Satoshi; Karashima, Shigehiro; Tsujiguchi, Hiromasa; Tsuboi, Hirohito; Miyagi, Sakae; Kometani, Mitsuhiro; Aono, Daisuke; Higashitani, Takuya; Demura, Masashi; Sakakibara, Hiroyuki; Yoshida, Akihiro; Hara, Akinori; et al. (Frontiers in Medicine, 2020)
Salt intake is one of the most important environmental factors impacting hypertension onset. Meanwhile, the potential roles of the gut microbiome (GM) in altering the health status of hosts have drawn considerable attention. Here, we aimed to perform an observational study to investigate the impact of intestinal bacterial flora in hypertensive patients with low-salt or high-salt intake. A total of 239 participants were enrolled, and their gut microbiomes, clinical and demographic details, as well as physiological parameters pertaining to the renin-angiotensin-aldosterone system and inflammatory cytokine profiles, were examined. The participants were classified into four groups based on the presence of different enterotype bacteria, as determined via cluster analysis, and salt intake: low salt/GM enterotype 1, low salt/GM enterotype 2, high salt/GM enterotype 1, and high salt/GM enterotype 2. Results show that the prevalence of hypertension was significantly lower in the low-salt/GM enterotype 2 group (27%) compared to the low salt/GM enterotype 1 group (47%; p = 0.04). Alternatively, no significant differences were observed in hypertension prevalence between the two high-salt intake groups (GM enterotype 1 = 50%, GM enterotype 2 = 47%; p = 0.83). Furthermore, The low-salt/GM enterotype 2 was higher in the relative abundances of Blautia, Bifidobacterium, Escherichia-Shigella, Lachnoclostridium, and Clostridium sensu stricto than the low-salt/GM enterotype 1. differed significantly between the GM enterotypes. These results suggested that consumption of a low-salt diet was ineffective in regulating hypertension in individuals with a specific gut bacteria composition. Our findings support the restoration of GM homeostasis as a new strategy for controlling blood pressure and preventing the development of hypertension.